Edukasi Permasalahan Pendidikan berbasis Data melalui Seminar Nasional HUT PGRI dan HGN ke-77 - Aunurrahman, Aunurrahman (Universitas Nusantara PGRI Kediri, 2024)
The imbalance of the number of public and private school teachers affects the performance of the teachers themselves. This needs to be a concern for teachers and stakeholders. Therefore, community service activities in the form of data-based education on education issues through Session 3 of the National Seminar on the Anniversary of the Indonesian Teachers Association and the 77th National Teachers' Day were held online via Zoom Application on November 10, 2022. The three stages of data-based education that were carried out were (1) preparation of titles and materials in the form of data on the number of teachers and teacher ratios, (2) presentation and interpretation of these data were carried out in front of teachers and stakeholders, and (3) presentation of recommendations based on education to stakeholders and teachers. These three stages were carried out and could show that data-based education has been done properly.